Clinical characteristics and management of 1572 patients with pyogenic liver abscess: A 12‐year retrospective study. (28th December 2020) - Yin, Dalong; Ji, Changyong; Zhang, Shugeng; Wang, Jiabei; Lu, Zhaoyang; Song, Xuan; Jiang, Hongchi; Lau, Wan Yee; Liu, Lianxin
Abstract: Background & aims: Pyogenic liver abscesses (PLA) are space‐occupying lesions in the liver that produce high morbidity and mortality. The clinical characteristics and prognosis of abscesses is different depending on the bacterial culture results and require different strategies for management. The aim of this study was to investigate the clinical characteristics and prognostic factors of patients with PLA. Methods: Clinical features, laboratory tests and etiology of PLA between 2006 to 2011 and 2012 to 2017 in a single hospital were retrospectively reviewed. The incidence and mortality of PLA caused by Escherichia coli and Klebsiella pneumoniae were compared and the risk factors for multiple organ dysfunction (MODS) and endophthalmitis were evaluated. Results: Among the 1, 572 PLA patients, the proportion with PLA increased from 333 (21.2%) in 2006‐2011 to 1, 239 (78.8%) in 2012‐2017 without any investigation and treatment procedure differences. K pneumoniae was the main isolate in analysed pus cultures (85.6%). The mortality rate of patients with K pneumoniae infection was lower in the latter period (6.7% vs 0.7%, P  = .035). Multivariate analyses revealed that age, fever, MODS and length of hospital stay were factors affecting poor prognosis (death + unhealed/uncured) in PLA patients after treatment and that cardiovascular disease, pleural effusion and pulmonary infection were risk factors for MODS, while diabetes mellitus was the only risk factor for endophthalmitis. Most patients (95.5%) with PLA recovered after abscess drainage/puncture and antibiotic therapy. Conclusions: Pleural effusion, fever, MODS and length of hospital stays were factors useful in predicting PLA outcomes.